Context Situation Analysis of Characters’ Utterance in “Little” Movie: Maxim of Quality Violation - Putu Devi Maharani; Putu Desi Anggerina Hikmaharyanti; I Gede Krismon Andika Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The research is concerning about the maxim violation of quality in which focuses in the portrayal of context situation that can be identified in the Little movie. The cooperative principles are roles or principles by Paul Grice’s theory (1975) in which used in the conversational analysis as purpose to make the idea or information easier to recognize and acceptable by the participants, speakers or the listeners in the conversation, where the types of the maxim include: maxim of quantity, maxim of quality, maxim of relevance and lastly the maxim of manner. The analyses are about the maxim violation in the Little movie applied the descriptive method in presenting data. In this analysis focuses on violation of the maxim quality, which can be identified 15 data of maxim violation of quality, and also concerning the portrayal of the context situation (field, tenor, and mode) based on Halliday & Hassan theory (1985) that consist of several scenes.   Keywords: Maxim Violation Quality, Movie, Grice’s Theory, Context Situation